FACTORS ASSOCIATED WITH POSTOPERATIVE COMPLICATIONS AFTER PANCREATODUODENECTOMY (WHIPPLE PROCEDURE) IN A SPECIALIZED CENTER: FACTORES ASOCIADOS A COMPLICACIONES DESPUÉS DE DUODENOPANCREATECTOMÍA CEFÁLICA (CIRUGÍA DE WHIPPLE) EN UN CENTRO ESPECIALIZADO - Cornejo, Jorge (2024)
ABSTRACT Introduction: Whipple procedure, also known as pancreatoduodenectomy (PD), is a widely used procedure for several types of peri-ampullary cancer. Objectives: To establish the factors associated with postoperative complications after PD in the Pancreas Surgery Service of the Edgardo Rebagliati Martins National Hospital in Lima, Peru.Methods: An observational, quantitative, analytical, cross-sectional, and retrospective study was carried out on 81 patients during the period from January 2017 to December 2019, who underwent PD. The dependent variable was postoperative complications and the independent variables were preoperative, perioperative, and postoperative variables. The medical records were reviewed. Logistic regression was performed to find the crude and adjusted ORs.Results: The mean age was 65.97±10.14 and the majority of patients were male. The most common postoperative complication was pancreatic fistula (34.6%). Factors associated with postoperative complications after PD were male sex (aOR: 4.46, 95% CI: 1.35-14.77), ampullary cancer (aOR: 6.92, 95% CI: 1.75-27.48), and soft consistency of the pancreas (aOR: 4.52, 95% CI: 0.07-0.58).Conclusions: The factors associated with postoperative complications after PD were male sex, ampulloma, and soft consistency of the pancreas.